The Application of Interactive E-Module Based on Android to Enhance Students’ Learning Outcome (A Useful Learning App in the Covid-19 Era) - Agustina, Yuli; Rosalia, Alvina Kevin (Adpebi Science Series, 2022)
Teaching and learning activities are currently adapting to the changing times and circumstances. The contemporary education system employs technology that facilitates teachers and students in teaching and learning activities and encourages students to engage in active and creative learning. Since the beginning of 2020, the COVID-19 virus has hindered face-to-face learning in schools. Consequently, learning activities have been conducted online for nearly a year using existing technologies. This demands independent student learning. This research seeks to develop Android-based interactive e-module products, assess the viability of Android-based interactive e-modules, and compare student learning outcomes before and after utilizing Android-based interactive e-modules for online learning. This research and development employed a modified version of the Borg and Gall Research and Development paradigm. Shapiro-Wilk testing was utilized for data analysis. The outcomes of this research and development were e-modules on the topic of Office Technology that have been deemed highly valid by subject matter and media experts and are acceptable for use in teaching and learning activities. After adopting Android-based interactive e-modules, students' learning results met or exceeded rigorous standards, as determined by a trial involving 26 students. Based on the study's findings, it can be stated that the Android-based interactive e-module is a viable and effective learning resource for enhancing student learning outcomes in Office Technology courses.